MODERN VIEWS ON THE PROBLEM OF GESTATIONAL DIABETES MELLITUS - Karimova, G.K.; Sharipova , N.M.; Tolibova , K.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The article review presents an analysis of publications that summarize international experience in the field of gestational diabetes mellitus diagnosis, which have caused controversy and debate. The results of all recommended screening tests, their advantages and disadvantages are described in detail. This article review clearly shows that a universal scheme that includes both the amount of glucose used in the glucose tolerance test and the norms, the increase of which indicates varying degrees of carbohydrate metabolism disorders, has not yet been developed.